IFN-I Mediates Dysfunction of Endothelial Progenitor Cells in Atherosclerosis of Systemic Lupus Erythematosus - Ding, Xuewei; Xiang, Wei; He, Xiaojie (Frontiers in Immunology, 2020)
Systemic lupus erythematosus (SLE) is a multi-system autoimmune disease including the cardiovascular system. Atherosclerosis is the most common cardiovascular complication of SLE and a significant risk factor for morbidity and mortality. Vascular damage/protection mechanism in SLE patients is out of balance, caused by the cascade reaction among oxidative stress, proinflammatory cytokines, Neutrophil Extracellular Traps, activation of B cells and autoantibodies and abnormal T cells. As a precursor cell repairing vascular endothelium, endothelial progenitor cells (EPCs) belong to the protective mechanism and show the reduced number and impaired function in SLE. However, the pathological mechanism of EPCs dysfunction in SLE remains ill-defined. This paper reviews the latest SLE epidemiology and pathogenesis, discusses the changes in the number and function of EPCs in SLE, expounds the role of EPCs in SLE atherosclerosis, and provides new guidance and theoretical basis for exploring novel targets for SLE treatment.